1994
DOI: 10.1177/096032719401300406
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Renal Changes in Workers Exposed to Soluble Nickel Compounds

Abstract: 1 Biochemical markers of kidney damage were examined in 14 male and 12 female workers highly exposed to soluble nickel compounds in a chemical plant. The results were compared to those obtained in 12 male and 12 female matched controls. 2 The concentration of nickel in urine of male and female workers averaged 5.0 and 10.3 μg g-1 creatinine, respectively. The mean duration of exposure in male and female workers was 25 and 15 years. 3 No differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…The variability of urine output on the urine Ni content was corrected with urine Effects of nickel exposure in nickel-plating workers 397 creatinine as per recommendation of international standard setting organizations such as the American Conference of Governmental Industrial Hygienists. The level of urine Ni reported in this study was similar to that reported in the study of Vyskocil et al [25]. Since the estimation of serum amylase is more sensitive compared with that of the amylase creatinine clearance ratio and serum lipase, the determination of serum amylase activity is used for assessing the exocrine pancreatic function in subjects exposed to Ni.…”
Section: Discussionsupporting
confidence: 89%
“…The variability of urine output on the urine Ni content was corrected with urine Effects of nickel exposure in nickel-plating workers 397 creatinine as per recommendation of international standard setting organizations such as the American Conference of Governmental Industrial Hygienists. The level of urine Ni reported in this study was similar to that reported in the study of Vyskocil et al [25]. Since the estimation of serum amylase is more sensitive compared with that of the amylase creatinine clearance ratio and serum lipase, the determination of serum amylase activity is used for assessing the exocrine pancreatic function in subjects exposed to Ni.…”
Section: Discussionsupporting
confidence: 89%
“…Mitigating toxicity concerns is especially important for Ni released in the body. There have been many studies investigating the non-cancer toxicity of nickel through various routes of exposure [20][21][22][23]. However, for implantable nickel-based devices, there have been no definitive tolerable intake values reported.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also might have been due to a direct interaction of these metals with the Na-citrate cotransporter, and at higher concentrations, this binding might be irreversible. High occupational exposure to Ni was found to induce renal tubular dysfunction in a chemical plant that produces several Ni compounds 33) . The time-weighted average exposure to Ni in the plant greatly exceeded the TLV of 0.05 mg/m 3 , was 0.75 mg/m 3 on average with a range of 0.04-2.86.…”
Section: Discussionmentioning
confidence: 99%
“…The time-weighted average exposure to Ni in the plant greatly exceeded the TLV of 0.05 mg/m 3 , was 0.75 mg/m 3 on average with a range of 0.04-2.86. Among Ni workers, significant elevations of lysozyme concentration, β 2 -MG and NAG activity have been reported 33) . Although the concentration of Co and Ni in this study (0-25 mM) might be too high, these exposure could be accidentally occurred.…”
Section: Discussionmentioning
confidence: 99%